Engaging with Dewey’s Valuation in Religious Education to Enhance Children’s Spirituality for Democratic Life - Statham, Audrey (Religions, 2021)
In this paper, we want to address how the educative growth of children’s spirituality within religious education can be better understood through Dewey’s theory of valuation. We would like to draw attention to the link between an education for authentic spirituality and the pursuit of a genuine democratic life, because education, even religious education, is always political. In doing so, we point to the urgency and importance of fostering spiritual education for children in the face of the current rise of authoritarianism throughout the world and the demise of authentic democratic life. In order for genuine democracies to survive and thrive, their citizens must be educated. Unlike indoctrination and propaganda, which control populations through manufacturing public opinion by which individuals are compelled to comply to an officially approved consensus, education is emancipatory by offering opportunity for dissensus. Emancipatory education enables individual citizens to initiate and participate in activities at the grass-roots level that pursue public and global goods, without waiting to be led by various authorities. Such an educated way of being, which is essential for democratic life, requires young people to be educated spiritually so that they are able to transcend the pressures to conform to public consensus and the will of authoritarianism, and instead to actively live their spirituality by undertaking activities that pursue the good, even when such activities are deemed to dissent from public opinion.